Temporal trend and epidemiological profile of accidents by venomous animals in Brazil, 2007-2019 - Souza, Tiago Cruz de (2022)
Objective: To analyze the temporal trend of accidents by venomous animals in Brazil from 2007 to 2019. Methods: Cross-sectional study carried out with data from the Notifiable Diseases Information System – Sinan. For the temporal analysis, the Prais-Wistein Linear Regression was used. The incidences by sex and age group, relative risk and lethality were calculated. Results: During the study period there were 2,102,657 cases of accidents by venomous animals. With the exception of snakebite, the other accidents showed an increasing temporal trend in most regions of the country. Scorpionism, snakebite and spider bites were responsible for 86% of accidents, mainly affecting men of working age. Snake (0.4%) and beetle (0.3%) accidents were the most lethal. Children were the main victims of accidents by bees, caterpillars and 'others'. Conclusion: Accidents by venomous animals showed an increasing temporal trend for most diseases and different epidemiological profiles.